Gain-scheduled control for LPV systems with scheduling parameters transmitted through a Markov channel⁎. Issue 26 (2018) - Palma, Jonathan M.; Morais, Cecília F.; Oliveira, Ricardo C.L.F.
Abstract: This work investigates the problem of H ∞ state feedback control for linear parameter varying systems whose dynamics is subject to jumps, emphasizing networked control problems in which the parameters and output or input signals may not be available due to packet loss. The networked control problem is formulated in terms of non-homogeneous Markovian jump linear systems and sufficient synthesis conditions are given in terms of parameter-dependent linear matrix inequalities, that can be solved using polynomial approximations and LMI relaxations. The main advantages of the proposed approach are the theoretical guarantees of stability and performance in the presence of switching (according to the packet loss) between robust and gain-scheduled controllers. The validity of the proposed technique is carried out by means of numerical examples, one of them based on a practical application.